2017
DOI: 10.1017/s000748531700030x
|View full text |Cite
|
Sign up to set email alerts
|

Quality control ofTelenomus remus(Hymenoptera: Platygastridae) reared on the factitious hostCorcyra cephalonica(Lepidoptera: Pyralidae) for successive generations

Abstract: Egg parasitoid rearing on factitious hosts is an important step to reduce costs and increase availability of the biocontrol agent but it requires quality control to achieve success in field conditions. To this end, this study evaluated the quality of Telenomus remus (Hymenoptera: Platygastridae) reared on Corcyra cephalonica (Lepidoptera: Pyralidae) for until 45 generations. In the first bioassay, we evaluated the body size of the laboratory-produced parasitoids. In the second bioassay, flight activity was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 37 publications
1
25
1
3
Order By: Relevance
“…However, local specificities need to be considered, e.g., the fact that, in the Americas, maize is often planted in large monocultures while most of the maize in Africa is cultivated by smallholder farmers in mixed systems. Challenges may also be encountered in the mass production of the parasitoid due to the inherent difficulty of rearing T. remus on its natural host and the need of a factitious host for mass production [23,26,48]. Since the T. remus populations established in Africa may have never encountered S. frugiperda until recently, and because it might have become adapted to completing development in yet unknown hosts, it may be less efficient on this host than populations from the Americas that have evolved with S. frugiperda during, at least, the past 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, local specificities need to be considered, e.g., the fact that, in the Americas, maize is often planted in large monocultures while most of the maize in Africa is cultivated by smallholder farmers in mixed systems. Challenges may also be encountered in the mass production of the parasitoid due to the inherent difficulty of rearing T. remus on its natural host and the need of a factitious host for mass production [23,26,48]. Since the T. remus populations established in Africa may have never encountered S. frugiperda until recently, and because it might have become adapted to completing development in yet unknown hosts, it may be less efficient on this host than populations from the Americas that have evolved with S. frugiperda during, at least, the past 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Although T. remus displays considerable potential for controlling S. frugiperda , it has proven to be challenging to find a suitable host for the mass-rearing of T. remus at an affordable cost in China [ 14 ]. Research has shown that T. remus can be reared successfully on the eggs of Corcyra cephalonica (Stainton) [ 15 , 16 ]. However, our preliminary experiments and other studies [ 14 ] conducted in China have indicated that T. remus cannot parasitize and develop in C. cephalonica eggs.…”
Section: Introductionmentioning
confidence: 99%
“…Females permanently exposed to parasitism tend to have lower longevity when compared to females deprived of hosts, it was observed that even after nine days of host absence there was no significant reduction in Telenomus remus (Nixon, 1937) (Hymenoptera: Platygastridae) parasitism rates (CARNEIRO et al 2009). In mass production, the survival capacity of natural enemies is one of the requirements for quality control (QUEIROZ et al 2017). Establishing the best exposure time is essential, as well as the ideal amount of parasitoid/host to guarantee greater longevity of the progeny, because, at high densities and longer contact time there will be less nutritional utilization by high competition, leading to less longevity (COSTA et al 2014b;BARBOSA et al 2016;CHEN et al 2018).…”
Section: Discussionmentioning
confidence: 99%